Bipolar symptoms questionnaires : preliminary observation of Icelandic translations - Áskell Friðriksson 1995-; Mirjam Yrsa Friðleifsdóttir 1995- (2024)
The process of monitoring mood fluctuations in bipolar disorder requires the expertise of a professional and appropriate assessment tools. In this study, we examined the Icelandic translations of four assessment tools for mood disorders: The Snaith-Hamilton Pleasure Scale, The Altman Self-Rating Scale, The Brief Quality of Life in Bipolar Disorder Questionnaire, and The Patient Health Questionnaire 9. Our objective was to compare clinical data from the bipolar disorder treatment department at a psychiatric hospital ward in Iceland (n = 32) with a healthy control group (n = 66). Our findings revealed differences in all questionnaires, but only two of them were considered significant. Therefore, further research and exploration are essential to improve the Icelandic translated versions of the assessment tools to effectively monitor mood fluctuations in individuals with bipolar disorder and intervene before episodes become too severe. Keywords: Bipolar disorder, mood fluctuations, Icelandic translation, assessment tools Ferlið að fylgjast með líðan fólks með geðhvarfasýki krefst sérfræðiþekkingar og sterkra matstækja. Í þessari rannókn könnuðum við fjögur matstæki sem nýlega hafa verið þýdd yfir á íslensku og notast er við hjá einstaklingum með lyndisraskanir: the Snaith-Hamilton Pleasure Scale, Altman Self-Rating Scale, Brief Quality of Life in Bipolar Disorder Questionnaire og The Patient Health Questionnaire 9. Tilgáta rannsóknarinnar var samanburður á klínískum gögnum einstaklinga með geðhvarfasýki frá Bipolar teymi Landspítalans á Íslandi (n = 32), við samanburðarhóp heilbrigðra einstaklinga (n = 66). Niðurstöður rannsókninnar sýndu mun á öllum matslistunum og aðeins tveir af þeim voru marktækir. Þar af leiðandi sýnir það mikilvægi þess að rannsaka matslistana til þess að betrum bæta þá lista sem hafa verið þýddir yfir á íslensku. Það er gríðalega mikilvægt að geta fylgst með líðan fólks með geðhvarfasýki til þess að geta gripið inn í áður en sjúkdómslotur verða of alvarlegar. Lykilorð: Geðhvarfasýki, líðan ...